2005
DOI: 10.1111/j.1365-277x.2005.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the provision of cooled filtered water in secondary school cafeterias increase water drinking and decrease the purchase of soft drinks?

Abstract: This pilot study indicates that active promotion of water drinking increased consumption of water by secondary school students. Further developments of the project are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 12 publications
2
66
1
1
Order By: Relevance
“…Our results were in line with conclusions by Loughridge and Barratt [29] who studied the impact of paid water provision at schools on cognitive determinants during 3 months. Loughridge and Barrat [29] had three intervention arms for their study. The first school received, besides the water coolers, promotion about the health benefits of drinking water by posters and verbal informing.…”
Section: Feasibilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Our results were in line with conclusions by Loughridge and Barratt [29] who studied the impact of paid water provision at schools on cognitive determinants during 3 months. Loughridge and Barrat [29] had three intervention arms for their study. The first school received, besides the water coolers, promotion about the health benefits of drinking water by posters and verbal informing.…”
Section: Feasibilitysupporting
confidence: 82%
“…Availability of calorie-rich drinks available from vending machines and canteens at school has increased during the last few years while an alternative healthy choice is not always available [17,[24][25][26][27]. The potential public health impact of reducing energy intake is described to be large [28], and, finally, we are aware of only one earlier pilot study in which water provision was perceived as being expensive by the pupils [29]. Larger intervention studies on reducing beverage sales by placing water coolers have not been presented yet.…”
Section: Introductionmentioning
confidence: 99%
“…16 Finally Loughridge and Barratt compared the impact of actively promoting water consumption along with improved water access to improving access alone, over a 3-month period in 3 British secondary schools, and found that promoting and increasing water access in schools increased water consumption more than solely increasing water access. 25 Each of these studies assessed interventions that both promoted improved water access and promoted water through classroom curricula. 16,18 The increase of 0.2 cups per student per day reported here is qualitatively similar to the approximately 0.3 cup increase per student per day in the study by Patel et al; however, unlike their study, the intervention studied here had no educational or behavioral components accompanying the increase in water availability.…”
Section: 24mentioning
confidence: 99%
“…Previous studies have found that improving access to water alone without decreasing access to SSBs does not decrease SSB consumption significantly [6,62].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that when school-aged children drink beverages high in sugar, this can displace their consumption of healthier beverages [68,69]. Improving access to appealing water has been shown to increase water consumption [6,40,62,63]. Water intake will improve children's school performance and overall health.…”
Section: Implication For Schools' Healthmentioning
confidence: 99%